The Effect of Read, Encode, Annotate, and Ponder (REAP) Strategy towards Student’s Reading Comprehension - Riandi Riandi; Ika Triana (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2019)
The research is aimed at finding out the effect of using Read, Encode, Annotate, Ponder (REAP) strategy toward reading comprehension in exposition text of the eleventh grade students of Islamic Senior High School Nurul’Amal Menes in 2019 Academic Year.The researcher collected from 54 students, by divided them into two classes, one class as the experiment class as much as 27 students and the other class as control class as much as 27 students. The population as much as 54 students of the eleventh grade of Islamic Senior High School Nurul’Amal Menes. The method of this research is experiment method. In this research, the researcher use pre-test and post-test to collect data. In which the test took form of the t-test, the data used to prove the hypothesis being proposed. In the pre-test, the standard deviation of experimental class was 6,88 and the standard deviation of control class was 7,47 while in the post-test the standard deviation of experimental class was 8,42 and the standard deviation of control class was 11,48. In the post-test of t-test, the researcher can conclude that of t count> table or 3,23> 1,671 so Ha = t count > t table therefore Ha is accepted and there is a significant effect of using Read, Encode, Annotate, Ponder (REAP) strategy toward students reading comprehension on exposition text.